Determining the Critical Nitrogen Application Rate for Maximizing Yield While Minimizing NO3−-N Leaching and N2O Emissions in Maize Growing on Purple Soil - Yuanyuan Liu; Yuanxue Chen; Dandan Peng; Huabin Lu; Ting Shuai; Ying Quan; Chunling Zeng; Kaiwei Xu (Agronomy, 2025)
Optimization of nitrogen (N) fertilizer application is essential to achieve higher crop yields at lower environmental costs. This study investigated the impacts of N application rates (0, 180, and 360 kg N ha−1) on maize productivity, N use efficiency (NUE), NO3−-N leaching, cumulative N2O emissions, and N surplus in maize growing in the purple soil of Southwest China through a 2-year field study. The critical N rate balancing yield optimization with reduced NO3−-N leaching and N2O emissions was identified. The results showed that grain yield initially increased linearly and then stabilized with increasing N rates, while NUE significantly decreased. NO3−-N leaching, N2O emissions, and N surplus exhibited quadratic increase. Regression analysis indicated that 158–163 kg N ha−1 achieved optimal yield while maintaining acceptable NO3−-N leaching and N2O emissions compared to 360 kg N ha−1. This range also enhanced NUE and minimized soil N residue.